Conceptualizing Religion (and Quasi-Religions): An elaboration on Freud in the “Light” of Kelsen. - Fittipaldi, Edoardo (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2024)
Sigmund Freud was one of the first thinkers to claim that some forms of Marxism have religious traits. This notwithstanding, in his Secular Religion Hans Kelsen discusses neither Freud’s treatment of Marxism nor his concept of religion. In Section 1, Fittipaldi briefly examines Freud’s treatment of the religious aspects of Marxism. Section 2 is dedicated to the reconstruction of Freud’s notion of religion as a polythetic conceptualization comprised of an ontogonical, a mellontological, a technological, a theistic, and a goneological component – a prototypical religion being comprised of all of them. Next, in Section 3, Fittipaldi discusses whether such a Freudian conceptualization involves the characterization of Buddhism, Marxism, and medicine as forms of quasi-religions – a characterization strongly rejected by Kelsen with regard to Buddhism and Marxism. Section 4 is dedicated to listing the differences between Freud’s and Kelsen’s notions of religion and – whenever possible – exploring their philosophical roots. Finally, Fittipaldi summarizes the results of this inquiry.